Phytoinhibition and formulation of allelopathic extract of Mikania micrantha Kunth ex H.B.K. as pre-emergent weed suppressant against Echinochloa colona (L.) Link - Lim, Chaw Jiang (2018)
Allelopathy delivers the concept of using allelochemicals elicited from donor plants into environment to influence the survival of receptor plants. Invasive plants having allelochemicals could provide low-cost, abundant and eco-friendly materials for controlling noxious weeds. In spite of that, the direct use of invasive plant extracts encounters major hurdles such as variation of bioactive chemicals not being identified, lack of optimal extraction, inadequate physicochemical properties and poor delivery system resulting in low efficacy of the natural products. This study aims to investigate the phytotoxicity, putative allelochemicals, extraction optimisation, pre-emulsion formulations and water-dispersible powders of the leaf extract of Mikania micrantha Kunth ex H.B.K. against a noxious weed, Echinochloa colona (L.) Link and the impact on productivity of rice plant, Oryza sativa L.. In phytotoxicity study, the leaf, stem and root (except M. micrantha) extracts of nine invasive plant species were evaluated against E. colona. Among the plant extracts, the leaf extract of M. micrantha showed 100% inhibition of germination of E. colona at the concentration of 100 g BDWE/L. The leaf extract was subjected to liquid chromatography-mass spectrometer (LC-MS) analysis to identify phytochemicals with possible inhibitory effect. Joint putative allelochemicals consisting of 16 phenolics and 4 aromatics were detected and protocatechuic acid was found contributed to 15.39% inhibition of germination. The leaves of M. micrantha were processed through extraction optimisation using response surface methodology (RSM). The optimal extraction condition was found at an extraction time of 262 min, a stirring speed of 259 rpm and an aqueous methanol of 95% v/v. In the development of pre-emulsion formulations, three polyalkoxylated fatty alcohol (PAFA)-based mixed surfactants PAFA-AS (alkyl sulfonate), PAFA-CB (cocamidopropyl betaine) and PAFA-APG (alkyl polyglucosides) were used to construct the pre-emulsions E1, E2 and E3 containing rapeseed oil methyl esters (ROMEs), water and sodium silicate. The pre-emulsions were diluted with water and agitated with an isothermal shaker to the weight fractions (Φw) of 0.8 and 0.6. In rheology study, these samples showed shear thinning, linear viscoelastic (LVE) (G’>G”) and strain softening (G”>G’) characters. In mesomorphic study, the samples E1, E2 and E3 promoted multilamellar vesicles, bicontinuous cubic phase and multilamellar phase, respectively. The pre-emulsions E1, E2 and E3 were incorporated with the leaf extract of M. micrantha to form the pre-emulsion formulations F1, F2 and F3. These pre-emulsion formulations exhibited higher stability against heat at a temperature of 54 oC than the non-formulated leaf extract. For product ease of application, the pre-emulsion formulations F1, F2 and F3 were loaded onto mercerised lignocellulosic fibre to produce water-dispersible powders WDP-F1, WDP-F2 and WDP-F3, respectively, and the non-formulated leaf extract powder WDP-EX was prepared for comparison. In release kinetics study, the formulated powders demonstrated initial burst and subsequent sustained release of phenolics achieved the amounts of 63.66 to 86.52% at 168 h, whereas phenolic release from the non-formulated powder was at the lowest amount of 41.98%. The particle releases from the formulated powders showed mean particle sizes were in the range of 87.56 to 103.27 nm whereas the mean particle size of 423.93 nm was observed from the non-formulated powder. In controlling the germination of E. colona, the formulated powders gave lower ED50 values in the range of 25.97-33.66 g WDP/m2 than the non-formulated powder at 132.00 g WDP/m2. In the glasshouse study, the formulated powders WDP-F1, WDP-F2 and WDP-F3 exhibited higher inhibition of germination, shoot height, fresh weight and dry weight of E. colona than the non-formulated powder WDP-EX and non-treated weedy control NWC. Notably, the sample WDP-F2 demonstrated the greatest inhibition of E. colona and statistically equivalent to commercial Satunil® and weed-free non-treated control NWF. Due to efficient controlling of E. colona by the formulated powders, the tiller height, tiller number, panicle number, fresh weight, dry weight, grain number and grain weight of O. sativa were increased in comparison to the non-formulated powder WDP-EX and non-treated weedy control NWC. The potential exploitation and formulation of the phytotoxic leaves of M. micrantha could pave the alternate to synthetic herbicide use in forging eco-friendly weed management.